Hamburger Schulen im "Dritten Reich" - Band 1 - Schmidt, Uwe (Beiträge zur Geschichte Hamburgs, 2010)
The present book by the Hamburg teacher and historian Uwe Schmidt on Hamburg schools in the "Third Reich" is the first comprehensive presentation of the school system in the Hanseatic city between 1933 and 1945. It is based on in-depth source research.The extensive study covers all types of schools and goes beyond the borders of the Hanseatic city before 1937: for the first time, it examines the school history of the former Prussian towns of Altona, Harburg and Wandsbek as well as other surrounding communities, which were added by the Gross-Hamburg Act in 1937.In addition to the content of this monograph, the qualified register of persons with biograms and, above all, the survey of the individual Hamburg schools and their history, which has been compiled with great effort, are particularly commendable, making this study a useful reference work.The work is divided into two parts: Volume 1 contains only the comprehensive presentation of the contents, while Volume 2 contains a listing of abbreviations, the list of schools from 1933 to 1945, statistical lists, references to sources, bibliography and sources, the registers (persons, subject and geographical index), the index of illustrations as well as information on authors and editors, the series and the Verein für Hamburgische Geschichte.